NEW MID-SEASON SPRING BARLEY CULTIVAR OMSKY 101 - P. N. Nikolaev; O. A. Yusova; N. I. Aniskov; I. V. Safonova; J. V. Ryapolova (Труды по прикладной ботанике, генетике и селекции)
Background. The primary task of plant breeding is to develop and introduce into production two-row mid-season barley cultivars for feed and food purposes, capable of generating a high and high-quality grain yield. The purpose of the study is to characterize the new two-row fodder spring barley cultivar ‘Omsky 101’ (bred at Omsk Agrarian Scientific Center) according to its grain quality, yield and resistance to a set of diseases.Materials and methods. The experimental part of the work was carried out from 2013 through 2018 on the experimental fields of Omsk Agrarian Scientific Center, located in the southern forest-steppe and steppe zones. The area of the plot was 10 m2; there were 4 replications. The seeding rate was 4 million viable seeds per 1 ha. Agricultural practice in the experiment was conventional for the West Siberian region. Mathematical data processing complied with B. A. Dospekhov’s guidelines.Results. In terms of productivity, the new promising cv. ‘Omsky 101’ is a high-yielding variety; on average, over the period of research, its yield significantly exceeded the level of the reference cv. ‘Omsky 95’ both in the southern forest-steppe zone (+0.55 t/ha) and in the steppe zone (+0.38 t/ha). The increase over cv. ‘Omsky 100’ was 0.29 and 0.59 t/ha when sown over autumn plowing and fallow, respectively. When compared with the reference ‘Omsky 95’, ‘Omsky 101’ showed a gain in the weight of 1000 grains (+5.3 g), grain unit weight (+44.0 g/l), and grain uniformity (+12.4%). Also, when compared with both the reference and ‘Omsky 100’, there was an increased content of protein (+1.0 and +0.9%, respectively) and starch (+1.3 and +1.5%, respectively) in grain. During the period of study, according to the maximum damage scores with various smut species, ‘Omsky 101’ showed low rates of susceptibility to false loose smut (3.5% on average) and covered smut (5.0%), which is lower than the reference and level with cv. ‘Omsky 100’. Loose smut virulence rate was medium (23.1%), which is level with the reference but exceeds ‘Omsky 100’. Conclusion. The new promising cultivar ‘Omsky 101’ is high-yielding, of high quality, and resistant to smut species. The cultivar has been submitted to State Variety Trials in the Ural (9), West Siberian (10) and East Siberian (11) regions.